2023
DOI: 10.3390/su15097242
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wood Ash and Sewage Sludge on Elemental Content in Hybrid Alder Clone

Abstract: In this study, the focus was on evaluating the effects of the initial treatment of wood ash and sewage sludge on hybrid alder clones’ aboveground biomass and elemental content. To measure the element concentrations in the tree rings, laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) was utilized, which is a valuable tool for dendrochemistry research, albeit with some challenges in accurate quantification. One important aspect of the study was the development and comparison of different “i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…It should be noted that all samples showed a significant increase in carbon content (4-5%) after the end of the growing season, as well as a significant change in δ13C, which has decreased in all cases. As in the previous study [11], no such sharp change in δ15N values was observed in the studied pine needles and ranged around 27%. δ13C values are usually associated with the…”
Section: Resultssupporting
confidence: 73%
“…It should be noted that all samples showed a significant increase in carbon content (4-5%) after the end of the growing season, as well as a significant change in δ13C, which has decreased in all cases. As in the previous study [11], no such sharp change in δ15N values was observed in the studied pine needles and ranged around 27%. δ13C values are usually associated with the…”
Section: Resultssupporting
confidence: 73%